Effect of CaCO3 Particles Size and Content on Impact Strenght of Kenaf/CaCO3/Epoxy Resin Hybrid Composites - Harini Sosiati; Cahyo Trisedyo Utomo; Iwan Setiono; Cahyo Budiyantoro (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2020)
Thermoplastic and thermoset polymer composites reinforced with kenaf fiber or CaCO3 have been extensively investigated. However, the study on the combination of kenaf fiber and CaCO3 reinforced epoxy resin is rare. This research discussed the effect of CaCO3 particle size and the ratio of kenaf to CaCO3 content on the impact strength of alkali-treated kenaf/ CaCO3/epoxy resin hybrid composites. Thirty % of the hybrid kenaf fibers and CaCO3 particles reinforced epoxy resin composites were fabricated by hand lay-up technique followed by cold press. Impact test of the composite specimens was conducted using a Charpy Impact test according to ASTM D 6110. The morphology of impact fracture surface was examined by scanning electron microscopy (SEM). The results showed that the impact strength of the hybrid composite increased with the decrease of CaCO3 particle size, and increasing the ratio of kenaf to CaCO3. Interfacial bonding between the reinforcement (kenaf and CaCO3) and epoxy resin matrix, the uniform dispersion of kenaf and CaCO3 within the epoxy resin matrix are two crucial factors influencing the impact strength of the composite.